(untitled) (International Journal of Engineering and Computer Science, 2014)
There have been recent interests in studying the goal behind a user’s Web query so that this goal can be used to improve the quality of a search engine’s results. The inference and analysis of user search goals can be very useful in improving search engine relevance and user experience. In this paper, main focus is on the survey of infer user search goal approaches in previous study. Additionally this paper projected a framework to search various user search areas for a query by clustering the feedback sessions. Feedback sessions are constructed from user click-through logs and can efficiently reflect the information needs of users. Additionally, a novel technique is projected to generate pseudo-documents to better represent the feedback sessions for clustering.